Cancer risk in the rubber industry: a review of the recent epidemiological evidence. Issue 1 (January 1998) - Kogevinas, M; Sala, M; Boffetta, P; Kazerouni, N; Kromhout, H; Hoar-Zahm, S
Abstract : OBJECTIVES: To examine the recent epidemiological evidence on cancer risk among workers in the rubber industry. METHODS: Epidemiological studies published after the last detailed review by the International Agency for Research on Cancer (IARC) in 1982 were reviewed. 12 cohort studies in nine countries that examined distinct populations of workers in the rubber industry, seven industry based nested case-control studies, 48 community based case-control studies in 16 countries, and 23 studies based on administrative data that reported risks for employment in the rubber industry were identified. RESULTS: Excess risks of bladder cancer, lung cancer, and leukaemia were found in most studies, with risks above 1.5 in about half of the studies. A moderate excess risk for laryngeal cancer was consistent across studies. Excess risks were found in a few studies for cancers of the oesophagus, stomach, colon, liver, pancreas, skin, prostate, kidney, brain, and thyroid, and for malignant lymphoma and multiple myeloma, but overall results were not consistent for these neoplasms. CONCLUSIONS: Magnitude of the observed risks varied considerably between studies, but overall the findings indicate the presence of a widespread moderate increased cancer risk among rubber workers. The most consistent results were for bladder, laryngeal, and lung cancer and for leukaemia. Excess risks were also found for other neoplasms but an evaluation of the consistency of the findings is difficult because of the possible selective reporting of results. Recent studies do not provide information associating specific exposures with cancer risk. The preventive measures taken in the rubber industry in recent years may decrease risks, but this has not been documented yet in epidemiological studies.